Successfull Level Of Artificial Insemination On Beef Cattle In Purwodadi District, Musirawas Regency - Sadjadi Sadjadi; Ririn Novita; Eko Triawan (Universitas Muhammadiyah Tapanuli Selatan, 2019)
he purpose of this study was to see the success rate of Artificial Insemination on beef cattle in Purwodadi district, Musi Rawas Regency. The parameters observed is Service per Conception (S/C), Conception Rate (CR), Non Raturn Rate (NRR) and Calving Interval (CI). Survey method isused in this study by taking all area of Purwodadi district as the observed area because of its livestock population then analysed by using Slovin Formula to obtain 93 samples. The results of this study concluded that the Conseption Rate (C/R) in Purwodadi District was very good because it was obtained 70.96%. Figures for S/C in Purwodadi sub-district showed an average of 1.4. As for the NRR value in Purwodadi Subdistrict, NRR(0-30) obtained a percentage of 70.96%. NRR(31-60) obtained 93.54% and NRR(61-90) obtained 100%. The value of the Calving Interval (CI) is very good, reaching an average of 14.7 or 14 months 7 days.Keywords: Artificial insemination, Purwodadi district, Beef Cattle, Success Rates